2021
DOI: 10.1111/cas.15079
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone is a natural product that potently inhibits YAP1/TAZ through promotion of reactive oxygen species accumulation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
(151 reference statements)
0
23
0
Order By: Relevance
“…For example, mitogen-activated protein kinases (p38 MAPK) and NF-κB signaling pathways are significantly attenuated by ALT, inhibiting cell viability and promoting cell apoptosis in lung cancer cell lines NCI-H1299 and Anip973 (Liu et al, 2019). And a recent study firstly reported that ALT could suppress the activation of YAP1/TAZ, leading to the inhibition of cancer cell growth (Nakatani et al, 2021). ALT could downregulate the serine/threonine kinase Aurora-A through directly binding to the interface pocket of Aurora-A-TPX2 complex, weakening several cancerassociated biological behaviors, including centrosome amplification, chromosomal instability and oncogenic transformations (Bhardwaj and Purohit, 2020;Nadda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mitogen-activated protein kinases (p38 MAPK) and NF-κB signaling pathways are significantly attenuated by ALT, inhibiting cell viability and promoting cell apoptosis in lung cancer cell lines NCI-H1299 and Anip973 (Liu et al, 2019). And a recent study firstly reported that ALT could suppress the activation of YAP1/TAZ, leading to the inhibition of cancer cell growth (Nakatani et al, 2021). ALT could downregulate the serine/threonine kinase Aurora-A through directly binding to the interface pocket of Aurora-A-TPX2 complex, weakening several cancerassociated biological behaviors, including centrosome amplification, chromosomal instability and oncogenic transformations (Bhardwaj and Purohit, 2020;Nadda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we screened a library of 29,049 low‐molecular‐weight chemical compounds using our previously described YAP1/TAZ‐TEAD reporter system (Nakatani et al, 2021; Nishio et al, 2016). As judged by: (1) inhibition of reporter activity (more than 50% decrease); (2) reduction in YAP1 protein levels (more than a 75% decrease); and (3) suppressed expression of YAP1 downstream target genes, we found nine compounds (out of 29,049) to be suitable candidates (Nakatani et al, 2021). Among these, four compounds (including the most potent agent) were alantolactone‐related molecules (Nakatani et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, in vivo administration of DMPCA markedly shrank the growth of T24 tumors in xenografted mice. (Nakatani et al, 2021). For the induction of Yap1 and Taz gene deletion in cultured iYap1/Taz DKO MEFs, cells were treated with 1 μM 4-hydroxytamoxifen (Tmx) for 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yes-associated protein 1 (YAP1) is one of the most key effectors of Hippo pathway. Generally, the upstream kinases of Hippo pathway form a complex and phosphorylate large tumor suppressor gene (LATS1/2), then the activated LATS1/2 kinase will phosphorylate YAP1 to inactivate it and also inhibit the transcriptional activity of YAP1 [13]. When the Hippo pathway is disordered, nonphosphorylated YAP1 will enter the nucleus and activate the transcription of proliferation-related molecules [14].…”
Section: Introductionmentioning
confidence: 99%